Пастернак и романская поэзия - Поздняков, А. Н.; Лебедева, И. В.
Данная статья посвящена переводам Б.Пастернака из французской и испанской литературы. Авторы статьи обращают внимание на особенности этих переводов. В статье рассматриваются принципы Пастернака-переводчика, а также причины обращения к тем или иным произведениям This article is devoted to Boris Pasternak’s translations from French and Spanish literature. The authors of the article pay much attention to the peculiarities of these translations. The article touches upon the principles of Pasternak as a translator, and also explains the reasons of appealing to one or another work.
Keywords: Литературоведение